A rare report of Rothia dentocariosa endocarditis. Issue 3 (4th May 2021) - Elkattawy, Sherif; Alyacoub, Ramez; Younes, Islam; Mowafy, Ahmed; Noori, Muhammad; Mirza, Muhammad
ABSTRACT: Rothia species are gram positive, round to rod-shaped bacteria that are normally oral and respiratory tract flora. They were first isolated in 1967 from dental caries. We present a 69-year-old male with no risk factors for aforementioned bacteria however was found to have thickened anterior leaflet of the mitral valve with a small isoechoic lesion consistent with vegetation on Transthoracic echocardiogram. Blood cultures grew pan sensitive Rothia dentocariosa. Patient was treated with long-term antibiotics. This case adds to the limited number of cases of Rothia dentocariosa Endocarditis.